Analisis Faktor - Faktor Yang Mempengaruhi Nilai Ekspor Kerajinan Kerang Di Provinsi Bali - Dias Pratama, I Made; Bendesa, I Komang (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
Shell crafts in Bali is a small-scale industry and among seventeen domestic handicraft export market . Export craft shells which are the result of the creativity of artists artisans in Bali. Purpose of this study was to determine the effect of mortgage interest rates , the US dollar exchange rate and the number of tourists visiting Bali simultaneously and partially on the export value of the province of Bali shell crafts and for the year 1993-2012. The analysis technique used is multiple linear regression analysis . The results of the data analysis later showed that mortgage interest rates , US dollar exchange rate and the number of tourists visiting Bali simultaneously significant effect on the value of exports of handicrafts shells Bali province in 1993-2012. Partially, lending rates and the number of tourists visiting Bali significant negative effect on the value of exports partially shell crafts while US dollar exchange rate and a significant positive effect on the value of exports of handicrafts partial shells in the province of Bali .
Keywords: value of shell crafts , exports , exchange rate , interest rate loans , the number of tourist